2013
DOI: 10.3109/01658107.2012.753913
|View full text |Cite
|
Sign up to set email alerts
|

Acute Reversible Charles Bonnet Syndrome Following Eye Patch Placement

Abstract: Charles Bonnet syndrome (CBS) is characterised by recurrent vivid visual hallucinations in the presence of normal cognition. We present a case of CBS secondary to eye patching following Pars Plana Vitrectomy with an unusually acute onset in a 48-year-old woman. She presented with formed visual hallucinations that started less than 30 min after patching of her left eye. The patch was removed after 2 d, and these hallucinations persisted 2 d following eye patch removal. It is important that the ophthalmic surgeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…It has been suggested that CBS risk is related more with the dynamic decrease of vision in sight-impaired patients or the acute decline of vision, rather than the low visual acuity itself (4). One of the most prevalent theories suggests that the acute visual impairment is a result of the hyperactivation of visual-related cortex, due to changes in neurotransmission during the early recovery period (1,3,5). The above theory could explain our case, in which the recovery period was short, with only 3 days of symptoms, and the cessation of the visual hallucinations indicated the end of it.…”
mentioning
confidence: 99%
“…It has been suggested that CBS risk is related more with the dynamic decrease of vision in sight-impaired patients or the acute decline of vision, rather than the low visual acuity itself (4). One of the most prevalent theories suggests that the acute visual impairment is a result of the hyperactivation of visual-related cortex, due to changes in neurotransmission during the early recovery period (1,3,5). The above theory could explain our case, in which the recovery period was short, with only 3 days of symptoms, and the cessation of the visual hallucinations indicated the end of it.…”
mentioning
confidence: 99%